The transformed equation is:
[tex](x-3)^2 = 23[/tex]
Step-by-step explanation:
We have to convert the equation in the form
[tex](x-p)^2 = q[/tex]
Given equation is:
[tex]x^2-6x-8 = 6[/tex]
Adding 8 on both sides
[tex]x^2-6x-8+8 = 6+8\\x^2-6x = 14[/tex]
In the given equation
a = x
b= ?
So,
[tex]2.x.b = 6x\\b =\frac{6x}{2x}\\b = 3\\[/tex]
So 3^2 will be added on both sides
[tex](x)^2-6x+ (3) = 14+ (3)^2\\(x-3)^2 = 14+9\\(x-3)^2 = 23[/tex]
Hence,
The transformed equation is:
[tex](x-3)^2 = 23[/tex]
Keywords: Quadratic equation, transformation
Learn more about quadratic equation at:
#LearnwithBrainly